Randomised controlled trial of intrapleural streptokinase in community acquired pleural infection - Davies, R; Traill, Z; Gleeson, F (1997)
Background - Standard treatment for pleural infection includes catheter drainage and antibiotics. Tube drainage often falls if the fluid is loculated by fibrinous adhesions when surgical drainage is needed. Streptokinase may aid the process of pleural drainage, but there have been no controlled trials to assess its efficacy. Methods - Twenty four patients with infected community acquired parapneumonic effusions were studied. All had either frankly purulent/culture or Gram stain positive pleural fluid (13 cases; 54%) or fluid which fulfilled the biochemical criteria for pleural infection. Fluid was drained with a 14F catheter. The antibiotics used were cefuroxime and metronidazole or were guided by culture. Subjects were randomly assigned to receive intrapleural streptokinase, 250 000 IU daily, or control saline flushes for three days. The primary end points related to the efficacy of pleural drainage - namely, the volume of pleural fluid drained and the chest radiographic response to treatment. Other end points were the number of pleural procedures needed and blood indices of inflammation. Results - The streptokinase group drained more pleural fluid both during the days of streptokinase/control treatment (mean (SD) 391 (200)ml versus 124 (44)ml; difference 267 ml, 95% confidence interval (CI) 144 to 390; p<0.001) and overall (2564 (1663) ml versus 1059 (502)ml; difference 1505ml, 95% CI 465 to 2545; p<0.01). They showed greater improvement on the chest radiograph at discharge, measured as the fall in the maximum dimension of the pleural collection (6.0 (2.7) cm versus 3.4 (2.7) cm; difference 2.9cm, 95% CI 0.3 to 4.4; p<0.05) and the overall reduction in pleural fluid collection size (p<0.05, twotailed Fisher's exact test). Systemic fibrinolysis and bleeding complications did not occur. Surgery was required by three control patients but none in the streptokinase group. Conclusions - Intrapleural streptokinase probably aids the treatment of pleural infections by improving pleural drainage without causing systemic fibrinolysis or local haemorrhage.